Intervention Effect of Group Counseling Based on Positive Psychology on Psychological Crisis of College Student. (12th August 2022) - Zhang, Zixi; Li, Yabo; Sun, Sailan; Tang, Ziye
Abstract : Objective . To analyze the intervention effect of group counseling based on positive psychology on psychological crisis of college student. Method . SCL-90 mental health screening was performed on second-year students in a college by cluster stratification. Among the detected students, 210 were included into the group after brief interview and randomly assigned to the experimental group and the control group. The control group was given conventional intervention measures, and the experimental group was given group counseling according to the interview results. One week before the start, on the day of the end of the intervention and 3 months after the end of the intervention, the mental health level of all subjects was evaluated by symptom self-rating scale, general well-being scale, and adolescent mental resilience scale. Results . The scores of two groups were different at different time points during the intervention. With the extension of time, the score of the self-rating symptom scale in the experimental group decreased significantly, while the total score of the self-rating symptom scale in the control group increased, with statistical significance P < 0.05 . Before the intervention, there was no significant difference in general well-being between the two groups P > 0.05 . At 3 months after the end of intervention, the total score of the general well-being scale in the experimental group increased, while that in the control group decreased, with statistical significance P < 0.05 . Three months after the end of the intervention, the total score of adolescent mental resilience scale in the experimental group increased. Conclusion . Group counseling from the perspective of positive psychology can effectively improve the mental health status of medical students with psychological crisis and improve their mental resilience.